2015
DOI: 10.1002/mrc.4243
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis, part 43. A theoretical and LIS/NMR investigation of the conformations of substituted benzamides

Abstract: A refined Lanthanide-Induced-Shift Analysis (LISA) is used with molecular mechanics and ab initio calculations to investigate the conformations of benzamide (1), N-methylbenzamide (2), N,N-dimethylbenzamide (3) and the conformational equilibria of 2-fluoro (4), 2-chloro (5) and N-methyl-2-methoxy benzamide (6). The amino group in 1 is planar in the crystal but is calculated to be pyramidal with the CO/phenyl torsional angle (ω) of 20-25°. The LISA analysis gave acceptable agreement factors (Rcryst ≤ 1%) for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Fluorine poses considerable problems in quantum mechanics and molecular modelling, the greater stability of cis vs. trans difluoroethylene being a classic case. 35 More recently we have commented on the small H-bonding energy in NHÁ Á ÁF 36 and OHÁ Á ÁF 37 interactions compared to quantum mechanical calculations. It is therefore of some interest to determine whether these results are supported by other physical measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorine poses considerable problems in quantum mechanics and molecular modelling, the greater stability of cis vs. trans difluoroethylene being a classic case. 35 More recently we have commented on the small H-bonding energy in NHÁ Á ÁF 36 and OHÁ Á ÁF 37 interactions compared to quantum mechanical calculations. It is therefore of some interest to determine whether these results are supported by other physical measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Abraham et al recently performed lanthanoid induced shift (LIS) NMR experiments on various amide containing organic molecules which showed that when a lanthanoid is complexed to the carbonyl oxygen of the amide moiety, pNMR shifts of 30-40 ppm can be achieved. 107 The cis proton was shifted significantly more than the trans proton, which is intuitive because the LIS paramagnetism is almost purely dipolar in nature and the lanthanoid distance to the cis proton was shorter than the distance to the trans proton. In the optimized structure of the paraCEST iron complex (FeL 3 ) 2+ the distances of the two protons from the paramagnetic iron center are also different, 4.55 for cis and 4.95 for trans, but this is not the cause of the observed shift difference.…”
Section: Application To Iron Paracest Complexesmentioning
confidence: 97%
“…The proposed mechanism proceeds through a ternary complex in which the trifluoroacetamidopyrazole ligand of Λ- Ir2 forms a double hydrogen bond with the nitroalkene, whereas one N , N -diethylcarboxamide moiety accepts a hydrogen bond from the indole NH group. Due to steric repulsion, the two ethyl groups force the carboxamide to rotate out of conjugation with the benzothiazole moiety . While multiple conformations are possible, only one leads to a catalytically productive ternary complex, and this conformational flexibility must be entropically unfavorable.…”
Section: Resultsmentioning
confidence: 99%